2013
DOI: 10.1016/j.lfs.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain changes in BDNF and S100B induced by ketogenic diets in Wistar rats

Abstract: These findings reinforce the importance of this diet as an inductor of alterations in the brain, and such changes might contribute to the understanding of the effects (and side effects) of KD in brain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Although, not statistically different, our findings are indicative of lower BDNF levels in both KD and KS control groups (7 and 8% lower, respectively). One other study described that feeding Wistar rats a KD for 8 weeks reduced BDNF levels in the striatum, but not the hippocampus (Vizuete et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although, not statistically different, our findings are indicative of lower BDNF levels in both KD and KS control groups (7 and 8% lower, respectively). One other study described that feeding Wistar rats a KD for 8 weeks reduced BDNF levels in the striatum, but not the hippocampus (Vizuete et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…A KD, but not a high fat or a low fat diet, led to a circadian shift in the expression of brain and liver BDNF, suggesting that a KD might impact (i) circadian activities, and (ii) the expression of BDNF [37]. However, the significance of neurotrophic factors as possible mediators of KD therapy are not yet clear, because in healthy rats a KD reduced BDNF levels in striatum, but not hippocampus, whereas the astrocyte neurotrophic cytokine S100β was not affected in the brain [38]. …”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Similarly, an eight-week KD provided to mice, as well as an omega-3 enriched KD; both led to approximately a 1.0ng/mL reduction in CSF S100β compared with controls and no change in S100β concentration in the hippocampus and striatum (137). Both studies (134,137) used experimental diets consisting of high amounts of lard, which is rich in SFA. However, a study analysing the hippocampal slices of rats fed a ketogenic diet found no significant difference in S100β after one or six weeks when compared with controls (138).…”
Section: S100β and Dietary Fatmentioning
confidence: 99%
“…Several reviews have discussed the potential application of the KD and KB in the treatment and prevention of neurodegenerative conditions including AD, through the management of dysfunctional insulin signalling and glucose metabolism (140,(188)(189)(190)(191). The reduced S100β levels observed in mice consuming a KD (134,137) is partly attributed to the production of BHB that can cross the BBB and provide energy to the brain as a safe alternative in the presence of impaired glucose metabolism (192). In addition, a KD in mice has also been shown to lower Aβ levels (193).…”
Section: Ketogenic Dietmentioning
confidence: 99%